PENERAPAN MEDIA PEMBELAJARAN POP-UP BOOK UNTUK MENINGKATAN HASIL BELAJAR SISWA DIKELAS V SD NEGERI 067259 KECAMATAN MEDAN JOHOR: Penelitian Tindakan Kelas - Evelyn Mine Angelina Br Barus; Rumiris Lumban Gaol (STKIP Subang, 2025)
This study aims to determine the effectiveness of applying the Pop-Up Book learning media to improve the learning outcomes of fifth-grade students at SD Negeri 067259 Medan Johor on the topic of spatial geometry. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results of the study showed a significant improvement in student learning outcomes. In the pre-cycle, the average score of students was 61.4 with 10 students completing the task and 15 students not completing it. In the first cycle, the average score increased to 74.2 with 17 students completing the task and 8 students not completing it. In the second cycle, the average score further increased to 83.6 with 23 students completing the task and 2 students not completing it. Based on these results, it can be concluded that the Pop-Up Book learning media is effective in improving student learning outcomes in the topic of spatial geometry.